Alkaloid and acetogenin-rich fraction from Annona crassiflora fruit peel inhibits proliferation and migration of human liver cancer HepG2 cells. - Allisson B Justino; Rodrigo M Florentino; Andressa França; Antonio C M L Filho; Rodrigo R Franco; André L Saraiva; Matheus C Fonseca; Maria F Leite; Foued Salmen Espindola (PLoS ONE)
Plant species from Annonaceae are commonly used in traditional medicine to treat various cancer types. This study aimed to investigate the antiproliferative potential of an alkaloid and acetogenin-rich fraction from the fruit peel of Annona crassiflora in HepG2 cells. A liquid-liquid fractionation was carried out on the ethanol extract of A. crassiflora fruit peel in order to obtain an alkaloid and acetogenin-rich fraction (AF-Ac). Cytotoxicity, proliferation and migration were evaluated in the HepG2 cells, as well as the proliferating cell nuclear antigen (PCNA), vinculin and epidermal growth factor receptor (EGFR) expression. In addition, intracellular Ca2+ was determined using Fluo4-AM and fluorescence microscopy. First, 9 aporphine alkaloids and 4 acetogenins that had not yet been identified in the fruit peel of A. crassiflora were found in AF-Ac. The treatment with 50 μg/mL AF-Ac reduced HepG2 cell viability, proliferation and migration (p < 0.001), which is in accordance with the reduced expression of PCNA and EGFR levels (p < 0.05). Furthermore, AF-Ac increased intracellular Ca2+ in the HepG2 cells, mobilizing intracellular calcium stores, which might be involved in the anti-migration and anti-proliferation capacities of AF-Ac. Our results support the growth-inhibitory potential of AF-Ac on HepG2 cells and suggest that this effect is triggered, at least in part, by PCNA and EGFR modulation and mobilization of intracellular Ca2+. This study showed biological activities not yet described for A. crassiflora fruit peel, which provide new possibilities for further in vivo studies to assess the antitumoral potential of A. crassiflora, especially its fruit peel.